Prevalence of HIV, Syphilis, and Hepatitis B and C Among Blood Donors in a Tertiary Care Hospital in Mexico - Ana María Mejía Domínguez; María de los Ángeles Soster-Contreras; Nayelli Campos-Morales; María del Rocío Sánchez-Díaz; Gabriel Chavira-Trujillo; Luis Pablo Cruz-Hervert; María Eugenia Jiménez-Corona (Venereology, 2024)
The prevalence of transfusion-transmissible infections (TTIs) among blood donors is critical for ensuring blood safety. Aim: To provide an updated assessment of TTIs at a tertiary care hospital in Mexico over a ten-year period. We conducted a retrospective cross-sectional study. Blood samples were analyzed from potential donors at tertiary care hospital between 2012 and 2022. Donors completed a questionnaire and were screened for HIV, syphilis, hepatitis B, and hepatitis C using nucleic acid testing and serological tests. Prevalence and trends were estimated. Among the 117,756 donors analyzed, 0.48% were positive for syphilis, with a significant annual decrease of −5.9% (p < 0.001), although notable fluctuations occurred, including a peak in 2021. HIV showed a significant annual increase of 9.8% (p = 0.029), with a peak in approximately 2019–2020. Hepatitis C maintained a stable trend, with a slight annual decrease of −5.6% (p = 0.170). Hepatitis B consistently decreased, with an annual decrease of −11.3% (p = 0.06). This study highlights the importance of continuous monitoring and screening of blood donors to ensure blood safety. These findings underscore the need for localized public health interventions, particularly to address the increasing incidence of HIV. Further research should focus on enhancing donor screening practices and public health strategies to reduce the prevalence of TTIs.